Delayed Intratumoral Hemorrhage after Drug-Eluting Bead Transarterial Chemoembolization for Hepatocellular Carcinoma - Kazue Shiozawa; Manabu Watanabe; Takashi Ikehara; Yu Ogino; Tomoko Umakoshi; Yasushi Matsukiyo; Michio Kogame; Teppei Matsui; Yoshinori Kikuchi; Yoshinori Igarashi; Yasukiyo Sumino (Case Reports in Oncology, 2014)
Transarterial chemoembolization (TACE) using a drug-eluting bead (DEB-TACE) for hepatocellular carcinoma (HCC) is a new treatment method. We report on a case of delayed intratumoral hemorrhage after DEB-TACE. An 81-year-old male with hepatitis C virus-related cirrhosis was diagnosed with a HCC of 35 mm in diameter in S5 detected by dynamic computed tomography (CT) and contrast-enhanced ultrasonography (CEUS). DEB-TACE with DC Bead® and epirubicin hydrochloride was performed because the patient declined to undergo surgical resection. The treatment was completed, and the course after DEB-TACE was favorable. However, right hypochondriac pain suddenly developed about 1 month after DEB-TACE. Unenhanced CT showed an increase of the tumor diameter and intratumoral high-intensity area, which was not enhanced in the arterial phase. CEUS performed at the time of right hypochondriac pain (5 weeks after DEB-TACE) showed nonenhancement of almost the entire tumor in the vascular phase. The cause of the symptom may have been DEB-TACE-associated intratumoral hemorrhage. Tumor hemorrhage has been reported after DEB-TACE with tumors >5 cm in diameter, and the tumor locations were subcapsular in all previous reports. There has been no case of a tumor with a diameter <5 cm distinct from the subcapsular, as was observed in our patient. Incomplete embolization might be the cause of the intratumoral hemorrhage experienced by this case presenting a few risks. To obtain the therapeutic effect of DEB-TACE while preventing the adverse events, it may be important to understand the characteristics of the beads and to apply the appropriate embolization to each individual case.